(untitled) (Indian Journal of Chemistry (IJC), 2026)
Megazol is a drug molecule used to treat acid-related diseases of the stomach. The B3LYP/6-311++G(d,p) level of theoretical calculations frequently employ Gaussian 16W software. Electronic structure analysis, FMO, NBO, MEP, Mulliken charge, vibrational frequency analyses, and electronic excitation determination through the IEFPCM model in various solvents are determined. NBO analysis explains that this is a stable molecule. By using Multiwfn 3.8 software, NCI, a shaded surface map, and hole electron interaction (HEI) with inter-fragment charge transfer analyses are determined. In the S6 excited state, electrons can move across p-linkers from an electron donor to an electron acceptor, according to HEI analysis. Heat maps are generated and discussed for the lowest six excitation states. Simulated scanning tunneling microscope analysis is also performed. Using the Shermo software, the impact of temperature on S, CV and CP is also ascertained. Theoretical UV-Vis and IR are discussed. The toxicity of the molecule is explained.